STABILIZING SURGICAL INTERVENTIONS IN THE TREATMENT OF DESTRUCTIVE PATHOLOGICAL HIP DISLOCATION AFTER HEMATOGENOUS OSTEOMYELITIS. (World Bulletin of Public Health, 2023)
The purpose of the study is to analysis of the outcomes of surgical treatment of children with pathological hip dislocation.
Keywords: osteomyelitis; hip; septic arthritis